Conceptual Bases of Business Activities' Management Grounded on Sustainable Development and Energy Self-Sufficiency of United Territorial Communities in the Context of the European Green Deal Implementation in Ukraine - YASNOLOB, Ilona; BOIKO, Stanislav; GORB, Oleg; POMAZ, Oleksandr; ZORIA, Oleksii; PYSARENKO, Svitlana; RUDYCH, Alla; DIADYK, Tetiana; DANYLENKO, Viktoriia; KOZACHENKO, Yuliia (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
The idea of developing energy self-sufficiency of the united territorial communities was presented in the article from the standpoint of the European Green Deal implementation in Ukraine, taking into account the national interests. The current situation in Ukraine was analyzed in the article, as well as the promising ways of European integration of Ukraine in the context of the European Green Deal, the conceptual foundations of energy self-sufficiency development in united territorial communities were defined, taking into account the existing and implementing new mechanisms to stimulate energy transformation in communities. The structure of basic components’ interrelation in developing and increasing energy self-sufficiency of the united territorial communities was proved. Peculiarities of the ways of Ukrainian united territorial communities’ development in the context of the European Green Deal implementation were investigated. The concept of the model of functioning of the State Agency of Ukraine on Management of Natural Resources for the requirements of developing energy self-sufficiency of the united territorial communities and practical recommendations on increasing energy self-sufficiency of the united territorial communities were worked out.